EL LIRIO ACUATICO EN MEXICO PROBLEMAS Y SOLUCIONES - JAIME GUADIANA, ALBERTO; CHAPA SALDANA, HECTOR (My University, 1978)
no
UNIVERSO
Keywords: LIRIO ACUATICO, MEXICO, PROBLEMAS, SOLUCIONES; CIENCIAS AGRARIAS; HORTICULTURA; FLORICULTURA